Minority Languages and the Majority Tongue: The Impact of Bilingualism in Education - Kalemi, Valbona; Shopi, Meleq (European Journal of Social Science Education and Research, 2026)
The presence of national minorities in Albania reflects both historical continuity and contemporary diversity. Official recognition between 2004 and 2017 of ethnic and ethno-linguistic groups-including Greek, Macedonian, Serbo-Montenegrin, Vlach, and Romani underscores their role in shaping cultural heritage. Among these, the Greek minority is the largest, settled mainly in southern Albania. This study examines the sociolinguistic use of Albanian within the Greek community, where Greek functions as the primary language and Albanian as a secondary one. The research focuses on conditions of Albanian use, levels of competence and the interaction between local dialects and the standardized Albanian. Methodologically, questionnaires and on-site observations in schools’ workplaces, everyday settings capture authentic bilingual practices. Findings highlight how Albanian is acquired, maintained, and evaluated, reflecting the processes of integration, language contact, minority rights and identity in Albania.
Keywords: Minority education, language contact, integration, sociolinguistic competence.